2019
DOI: 10.1101/834226
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Frequency selectivity of persistent cortical oscillatory responses to auditory rhythmic stimulation

Abstract: Rhythmic stimulation, either sensory or electrical, aiming at entraining oscillatory activity to reveal or optimize brain functions, relies on a critically untested hypothesis: it should produce a persistent effect, outlasting the stimulus duration. We tested this assumption by studying cortical neural oscillations during and after presentation of rhythmic auditory stimuli. Using intracranial and surface recordings in humans, we reveal consistent neural response properties throughout the cortex, with persisten… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 108 publications
(228 reference statements)
2
2
0
Order By: Relevance
“…In the present work, we studied a well-characterized auditory evoked brain response, and selected analyses like frequency tracking that are unlikely to introduce artifactual oscillations (as might narrowband filtering or broad spectral analysis). Our data are consistent with prior reports of poststimulus FFR aftereffects in EEG data (Xu and Ye, 2015), and with recent data also documenting similar aftereffects from intracerebral electrode cortical recordings and cortical MEG in humans in the 60-80 Hz range, similar to the stimuli used here (Lerousseau et al, 2019;Ross et al, 2020). Taken together, these convergent findings provide strong evidence for entrainment, and our data furthermore indicate that it is a pervasive feature of auditory processing in subcortical nuclei as well as cortex.…”
Section: Discussionsupporting
confidence: 93%
“…In the present work, we studied a well-characterized auditory evoked brain response, and selected analyses like frequency tracking that are unlikely to introduce artifactual oscillations (as might narrowband filtering or broad spectral analysis). Our data are consistent with prior reports of poststimulus FFR aftereffects in EEG data (Xu and Ye, 2015), and with recent data also documenting similar aftereffects from intracerebral electrode cortical recordings and cortical MEG in humans in the 60-80 Hz range, similar to the stimuli used here (Lerousseau et al, 2019;Ross et al, 2020). Taken together, these convergent findings provide strong evidence for entrainment, and our data furthermore indicate that it is a pervasive feature of auditory processing in subcortical nuclei as well as cortex.…”
Section: Discussionsupporting
confidence: 93%
“…In any event, the across-frequency band results for beta and alpha combined are further in line with a recent related report by Griffiths et al (2019), who also showed an effect spanning both frequency bands, although at a slower stimulation rate [38]. Directly relevant, most recent MEG work by Lerousseau and co-workers [50] presents with yet differing results with respect to the oscillatory modulations in the relevant frequency bands in question. In their study of passive listening to a regular beat in the relevant range, in fact of identical tempo to ours (2.5 Hz), the authors found no beat-based modulation in the beta nor in the alpha band, but rather an overall suppression of activity across both bands in the auditory cortex.…”
Section: Beat-based Modulations In Oscillatory Powersupporting
confidence: 90%
“…These findings are essential in showing that neural entrainment is not solely a bottom-up brain response to exogenous periodicities, it also reflects an endogenous temporal structure that is experienced by the listener. In fact, oscillatory dynamics can be measured in the absence of exogenous stimulation and resonate during and after rhythmic (Cason et al, 2015;Falk et al, 2017;Pesnot Lerousseau et al, 2021) and non-rhythmic (Teng et al, 2018) stimulation. Such intrinsic spontaneous oscillators support the biological and psychological needs for adaptability and stability.…”
Section: Modulation Of Endogenous Oscillations: Uncoupled Couplingmentioning
confidence: 99%